Plant nutrient supply alters the magnitude of indirect interactions between insect herbivores: From foliar chemistry to community dynamics. (3rd February 2020) - Han, Peng; Becker, Christine; Le Bot, Jacques; Larbat, Romain; Lavoir, Anne‐Violette; Desneux, Nicolas
Abstract: Density‐ and trait‐mediated indirect interactions (DMIIs and TMIIs respectively) are important drivers of community dynamics but how plant nutrients (bottom‐up effects) affect the magnitude of such indirect interactions has been scarcely addressed. To assess the impact of bottom‐up forces on indirect interactions, we carried out laboratory and greenhouse experiments manipulating plant nutrient supplies in a four‐species diamond food web consisting of a plant (tomato), two phytophagous insects (a leafminer and an aphid) and a predator (a mirid bug) attacking both herbivores. Multiple negative indirect effects of the leafminer occurred towards the aphid. The presence of its eggs negatively affected aphid population growth through increased predator abundance (DMIIs), and larval herbivory slowed down aphid development and negatively modulated aphid behaviours, for example they spent less time feeding (TMIIs), likely owing to enhanced plant chemical defences and/or decreased plant nutritional quality. Moreover, the low plant nutrient supply further magnified TMIIs. Synthesis . Abiotic factors modulated predator‐ and plant‐mediated indirect interactions among herbivorous community members. Our study highlights the importance of using a holistic approach, from foliar chemistry to community dynamics, for disentangling interspecific interactions in a simple food web. Abstract : Abiotic factors modulated predator‐ and plant‐mediated indirect interactions among herbivorous community members. Our study highlights the importance of using a holistic approach, from foliar chemistry to community dynamics, for disentangling interspecific interactions in a simple food web.